The impact of a proposed multimedia program in the development of some basic handball skills among high school students - henna hachmi (sports creativity, 2025)
The objectif of the study is to find out the impact of the proposed multimedia- based educational program on the development of some basic skills in handball among secondary school students, since the teacher is one of the most important components of the educational system and the key to success or failure in the curriculum is the direct communication tool for the student. In the end entrusted to the task of achieving the goals and the desired educational goal. The effectiveness of the professor and his skill depends on the success of the educational system of curricula, and methods of teaching and educational management in terms of translating goals and means for planning to the field of implementation. But this can only be achieved through the development of means or media used in the completion of the quota where the professor to introduce modern technical means in the education of some basic skills because the student can not learn those skills accurately, depending on the traditional method that has become useless because the student wants information necessary to master that skill , And this is what is achieved by multimedia and this is what leads us in our research to highlight the effectiveness of the use of multimedia in learning some basic skills in handball